Estudo da rigidez, da deformação permanente e da fadiga de misturas asfálticas com ligantes convencionais e modificados - Boeira, Fernando Dekeper (2018)
In Brazil, there are two most recurrent defects found on highways: permanent deformation and cracking due to fatigue. Among the most varied causes, the formation and propagation of cracks in the asphalt coating occurs as a consequence of the repeated loading caused by the traffic that, over time, will drastically reduce the service life of the pavement, for example, facilitating the penetration of water into the granular layers of the pavement. structure and accelerating its deterioration. Efficient methods to predict the performance of asphalt mixtures in many countries of Europe and North America are already a consolidated reality, as is the case of the tool that allows interpretation of the viscoelasticity of asphalt mixtures, the Complex Modulus, which, in Brazil, is still very restricted to the academic, as well as the methods to performance permanent deformation and fatigue damage predict. The aim of this study is to contribute to the implementation and dissemination of the new the Direct Tension Cyclic Fatigue Test. And to study the behavior of asphalt mixtures with respect to the influence of the type of asphalt binder used, the mix design method and the particle size distribution with respect to its viscoelastic properties, permanent deformation and fatigue damage. For the accomplishment of the study the parameters of the Marshall and SUPERPAVE design methods were obtained with different aggregate gradations, two of the band B and two of the band C of the DNIT 031/2006-ES specification. Two bands, B and C, which were composed by trial and error in such a way that meet the specification, and two by the Bailey method, also in band B and band C, for the three asphaltic binders. Mechanical tests were used in this study to characterize the behavior of asphalt mixtures in terms of permanent deformation, viscoelastic behavior and especially the behavior with respect fatigue damage. They were used to evaluate the deformability (Resilience Module and Complex Modulus), and to evaluate the resistance (Indirect Tensile Strength, Flow Number and Direct Tension Cyclic Fatigue). Regarding the results, the Marshall mixtures had higher binder contents than the SUPERPAVE mixtures. In the results of Flow Number it was showed a significant influence of the type and content of the binder. The greater the amount of modification in the asphaltic binder by SBS polymer the greater the FN of the blends. For the Direct Tension Cyclic Fatigue test, the equipment implementation and the calculation routine were adequate, with full capacity to characterize the fatigue of asphalt mixtures. Unlike the results of permanent deformation, for fatigue, the effect of binder modification is not so clear. The utilization of the Fatigue Area Factor using the failure envelopes based on the Gr rupture criterion presented good indications for the classification of asphalt mixtures.